Optimizing Sustainable Broiler Production Through Elasticity Analysis: Evidence from Partnership-Based Closed House Systems - Reynaldi Rizalianus Hutama; Dewi Masyithoh; Inggit Kentjonowaty; Arsalan Fadlan Aziz; Muhammad Helmi; Budi Hartono; Puji Akhiroh; Nanang Febrianto (Postgraduate, University of Mataram, 2026)
The broiler industry plays a critical role in Indonesia’s food supply chain, yet productivity challenges persist, particularly in partnership-based closed-house systems. This study examines the influence of production inputs on broiler output using data from 50 contract farmers in Malang Regency through multiple linear regression, LASSO regression, and elasticity analysis. Severe multicollinearity was detected among chicken population, feed quantity, and total cost (VIF > 100), addressed using LASSO regularization. The resulting adjusted R² of 0.9994 is unusually high for cross-sectional socio-economic data and should therefore be interpreted cautiously due to potential overfitting. Regression results indicate that number of employees, depletion rate, and performance index significantly contribute to production volume, while chicken population and feed quantity have negative and statistically non-significant coefficients. Elasticity analysis shows that significant input variables, except performance index, are inelastic (coefficients < 1), whereas performance index is elastic (1.899). The counterintuitive negative coefficients for population and feed, alongside the positive depletion coefficient, suggest residual multicollinearity and conceptual overlap between performance index and other inputs, which future work should address through model re-specification. These findings nonetheless highlight labor management, mortality control, and performance monitoring as priority areas for improving productivity in partnership-based closed-house broiler systems in Indonesia.